KAJIAN ASPEK EKONOMI PENGELOLAAN HASIL HUTAN DI HULU DAS WAE RIUPA KABUPATEN SERAM BAGIAN BARAT - Rosita M. Elly; Gun Mardiatmoko; Debby Vemiancy Pattimahu (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
Forest assessments to quantify Total Economic Valueave been carried out in many countries. The development of forest valuation, apart from forest products that have a market goods. Nowdys various methods of calculating forest product economic value that cannot be determined by the market system (non market goods) have developed. This study examined the economic aspects of forest product management in the upper watershed of Wae Riupa, West Seram Regency. The results showed of calculating the value of direct use Direct use Valuethe value of indirect use (indirect use-value) of Rp. 1. 645,920.00, -, the option value is Rp. 458.642,449, -, optional benefits of Rp. 11. 384,651,002, and the total economic value (TEV) of 13.489,213,451, -.ost of the potential forest products used and managed by the community in Rambatu Village come from forests, including timber forest products, various kinds of rich animals, non-timber forest products, and environmental services.